Management of Village Finance to Achieve Good Governance in Talagasari, Garut - Riki Ismail Barokah (CIC Lembaga Riset dan Konsultan Sosial, 2020)
This study aims to explore village authority in village financial management to realize village governance in accordance with the principles of Good Governance. One of the financing for the Village Government program is the Village Fund Budget (ADD). The research method used is descriptive analysis to get a clear picture by examining secondary data. Secondary data is obtained through literature studies from primary legal materials and secondary legal materials related to regional autonomy in villages in the management of Village Government, particularly with regard to the performance of Village-Owned Enterprises based on Law Number 6 of 2014 concerning Villages. The data obtained from this study were analyzed juridically normative with a statutory approach. The results showed the accountability of the village head in managing village finances. In exercising the power of village financial management, the village head authorizes part of his power to the Village apparatus. (2) The village head as the holder of the village financial management power as referred to in paragraph (1), has the authority to: a. establish policies regarding the implementation of APBDesa; b. determine PTPKD; c. determine the officer who collects village revenue; d. approve expenditures for activities stipulated in APBDesa; and e. take actions that result in spending at the expense of the Village Budget. The factors that become obstacles in Talagasari, namely the lack of information and lack of direction in the distribution of ADD, so that it contributes low to community empowerment.